Effect of Fleet Availability and Controlling on Delivery Accuracy: Case Study at PT. Cardig Logistics Indonesia - Astri Rumondang Banjarnahor; Agus Tri Harjono; Agus Setiawan (Jurnal Manajemen Bisnis, 2021)
This study aimed to determine the effect of fleet availability and control on the smooth delivery of PT. Cardig Logistics Indonesia. The survey method is used as a way to collect primary data. The population is taken from employees who work in the operational section and get a sample of 30 people. The writer used a descriptive statistical analysis method, multiple linear regression, correlation coefficient, determination coefficient, or determination to test the research hypothesis to conduct this research. The results showed that the availability of the fleet (X1) and controlling (X2) on the smooth delivery (Y) of PT. Cardig Logistics Indonesia has a positive and significant effect. From the research result, the more dominant is the variable of fleet availability.